(untitled) (Marketing Journal, 2025)
This article highlights the role and importance of the securities market as one of the modern methods of financing joint -stock companies. Today, in a market economy, the need to attract external financial resources to ensure sustainable financial growth of enterprises is increasing. In particular, the issue of open shares, the issuance of bonds, and the use of secondary market operations are recognized as important sources of attracting investments for joint -stock companies. The article provides an in -depth analysis of the structure, functions, impact on the activities of joint -stock companies, and their role in increasing the financial soundness of these companies. It also examines the reforms being implemented to develop the securities market in Uzbekistan , the regulatory framework, and existing problems. Factors such as bureaucratic obstacles faced by joint -stock companies in financing through securities, low investor confidence, and lack of liquidity in the market were analyzed, and practical prop osals were developed to eliminate them.